A diet high in fat and fructose adversely affects osseointegration of titanium implants in rats - Shalinie King; Carina Baptiston Tanaka; Dean Ross; Jamie J. Kruzic; Itamar Levinger; Iven Klineberg; Tara C. Brennan‐Speranza (Wiley, 2020)
Abstract Objectives Diet‐induced metabolic dysfunction such as type 2 diabetes mellitus increases the risk of implant failure in both dental and orthopaedic settings. We hypothesised that a diet high in fat and fructose would adversely affect peri‐implant bone structure and function including osseointegration. Materials and methods Thirty female Sprague‐Dawley rats were divided into three groups (n = 10), control group (normal chow) and two intervention groups on a high‐fat (60%), high‐fructose (20%; HFHF) diet. Titanium implants were placed in the proximal tibial metaphysis in all groups either before commencing the diet (dHFHF group) or 6 weeks after commencing the diet (HFHF group) and observed for an 8‐week healing period. Fasting blood glucose levels (fBGLs) were measured weekly. Structural and functional features of the peri‐implant bone, including bone‐to‐implant contact (BIC), were analysed post euthanasia using microcomputed tomography, pull‐out tests, and dynamic histomorphometry. Results The fBGLs were unchanged across all groups. Peri‐implant trabecular bone volume was reduced in the HFHF group compared with controls (p = .02). Percentage BIC was reduced in both HFHF group (25.42 ± 3.61) and dHFHF group (28.56 ± 4.07) compared with the control group (43.26 ± 3.58, p < .05) and reflected the lower pull‐out loads required in those groups. Osteoblast activity was reduced in both intervention groups compared with the control group (p < .05). Conclusion The HFHF diet compromised osseointegration regardless of whether the implant was placed before or after the onset of the diet and, despite the absence of elevated fBGLs, confirming that changes in bone cell function affected both the initiation and maintenance of osseointegration independent of blood glucose levels.